Profile of Indians died abroad: analysis of secondary data of human remains arrived at point of entry in Mumbai - Gaikwad, Pragati B.; Khandare, Kanchan P.; Dan, Amitabha; Jalaluddeen, Mohammed; Pasi, Achhelal R.; Singh, Sujeet Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: According to Ministry of External Affairs (MEA) – India, in 2015 a total of 8315 people of Indian origin died abroad and more than 65% were from United Arab Emirates (UAE) and Saudi Arabia. Present study was conducted to study the demographic profile and cause of death in case of persons died abroad. Methods: Present descriptive study was conducted in APHO, Mumbai and it was a secondary data analysis. All records during 1st January 2016 to 31st December 2016, available in the office of APHO Mumbai related to clearance of dead body were reviewed. Data analysis was done in line with objectives by using Microsoft Excel. Qualitative data was presented by using number and percentages while quantitative data was presented by using mean and standard deviation. Results: During the reporting period 534 dead bodies arrived at CSMI Airport. Average age of the person died abroad was 48.4 years and more than 85% were males. In more than 65% of cases the reported cause of death was heart related including cardiac arrest and road traffic accidents. More than 50% of dead bodies were from gulf countries. Conclusions: Death was reported in a significant number of Indians travelling abroad and most of them were relatively young. Heart diseases including cardiac arrest and road traffic accidents were the commonest reported cause of death. A targeted health communication strategies for modification of life style and behavior change is recommended for persons travelling abroad.